Follicle Stimulating Hormone and Anti-Müllerian Hormone per Oocyte in Predicting in vitro Fertilization Pregnancy in High Responders: A Cohort Study - Weghofer, Andrea; Kim, Ann; Barad, David H.; Gleicher, Norbert (PLOS ONE, 2012)
Background Follicle stimulating hormone (FSH) and Anti-Müllerian hormone (AMH) are utilized to differentiate between good and poor response to controlled ovarian hyperstimulation. Their respective roles in defining functional ovarian reserve remain, however, to be elucidated. To better understand those we investigated AMH and FSH per oocyte retrieved (AMHo and FSHo). Methodology/Principal Findings Three-hundred and ninety-six women, undergoing first in vitro fertilization cycles, were retrospectively evaluated. Women with oocyte yields >75th percentile for their age group were identified as high responders. In a series of logistic regression analyses, AMHo and FSHo levels were then evaluated as predictive factors for pregnancy potential in high responders. Patients presented with a mean age of 38.0±5.0 years, mean baseline FSH of 11.8±8.7 mIU/mL and mean AMH of 1.6±2.1 ng/mL. Those 88 women, who qualified as high responders, showed mean FSH of 9.7±6.5 mIU/mL, AMH of 3.1±3.1 ng/mL and oocyte yields of 15.8±7.1. Baseline FSH and AMH did not predict pregnancy in high responders. However, a statistically significant association between FSHo and pregnancy was observed in high responders, both after univariate regression (p = 0.02) and when adjusted for age, percentage of usable embryos, and number of embryos transferred (p = 0.03). Rate of useable embryos also significantly affected pregnancy outcome independently of FSHo (p = 0.01). AMHo was also associated with clinical pregnancy chances in high responders (p = 0.03) and remained significant when adjusted for usable embryos and number of embryos transferred (p = 0.04). Conclusions AMHo and FSHo are predictive of pregnancy potential in high responders, but likely reflect different responsibilities in recruitment and maturation of growing follicle cohorts.